Water-Cooled Chiller Terintegrasi Heat Recovery System pada Industri Perhotelan di Bali - Sucipta, Made; Oka Jeve, Ida Bagus; Astawa, Ketut (Jurnal Energi Dan Manufaktur, 2020)
Performance testing of water-cooled chiller integrated with a heat recovery system has been carried out at a hotel in Bali. After commissioning, testing is carried out for 2 days to determine the readiness of the components in operation. The coefficient of performance which is the reference in this study is used to determine the performance of the system with a capacity of 275 tons of refrigeration which is divided into the coefficient of performance of the refrigeration system and the coefficient of performance of the total integrated system. Data was collected with 8 hour intervals starting at 06.00, 14.00, and 22.00 Wita every day. This condition is based on the prediction of the cycle of changes in energy use in the hotel, which includes breakfast, hotel check-in and bedtime. From the research results, it was found that with the condition and situation of the hotel were not measured properly and the occupancy rate of the hotel which was not yet maximal resulted in a greater refrigeration capacity on the second day, but this was also followed by a large demand for compressor power. Although in the end the coefficient of performance was slightly larger than day 1. It was also found that the greatest need for heat transfer rate is required at 22.00 Wita during the 2-day test. This is possibly due to the need for hot water for hotel guests to shower at night. In general, an increase in the coefficient of performance is still possible if there is an increase in hotel occupancy rates.